Analysis of Factors Causing Depression among Administrative Staff - Marselina Bellanita Reda; Marselino Kharitas Purna Abdi Keraf; Dwita Anastasia Deo; Nicholas Edwin Handoyo (Journal of Health and Behavioral Science, 2026)
Occupational depression is a global issue impacting productivity, yet attention to administrative staff in higher education remains limited. A preliminary survey at Nusa Cendana University indicated that 28% of administrative staff exhibited symptoms of depression. This study aimed to analyze the determinants of such depression by examining psychological well-being, work-life balance, and work environment. Using a qualitative design, data were collected through in-depth interviews with six administrative staff members identified with depression and analyzed using Reflexive Thematic Analysis. Results identified three key themes: personal life interference with work because of family dysfunction, workplace ambivalence as a stressor, emotional escape, and manifestations of psychological collapse. It is concluded that depression among administrative staff represents a complex interaction between personal life issues and institutional pressures. These findings highlight the urgency of interventions through the development and implementation of policies that support mental health.